Baseline distributions and sources of polycyclic aromatic hydrocarbons (PAHs) in reef-associated sediments of Vembar group of Islands, Gulf of Mannar, India. (October 2021) - Pradhap, D.; Gandhi, K. Sanjai; Krishnakumar, S.; Neelavannan, K.; Radhakrishnan, K.; Saravanan, P.
Abstract: The study aims to investigate the source and concentration of PAH fractions in the reef sediments of the Vembar group of Islands, Gulf of Mannar, India. The concentration of PAHs ranged from 0.36 to 15.98 ng/g. The reef environment was less contaminated with low-molecular-weight PAH fractions. The accumulation of the LMW-PAH fraction was very less, whereas the HMW fraction was derived from pyrolytic sources. The level of low and high molecular weight PAHs was lower than the level of Effective Range Median (ERM) and Effective Range Low (ERL).The calculated total TEQ value ranged from ND to 10.24 ng/g in the reef sediments. Highlights: The present investigation was carried out in the reef sediments to study the source and distribution of PAHs The reef associated surface sediments was dominated by HMW ring PAHs (Naphthalene and Phenanthrene) The PAH fractions were derived from pyrolytic sources especially coal incinerating power plants. The level of PAH fractions was less than the other comparative studies around the world.